A taste of Vietnam : all about Vietnamese foods and cooking - Video Education Australasia; Dinh, Agnes; Bretherton, Liz; Vallis, Adrian (Bendigo, Vic.: Video Education Australasia, 2022)
Describes and explains the range of Vietnamese produce and ingredients. Selected recipes, with easy to follow step-by-step instructions are demonstrated